A cross-culture study on older adults' information technology acceptance. (12th September 2011) - Wang, Lin; Rau, Pei-Luen Patrick; Salvendy, Gavriel
This study investigated cultural differences in older adults' information technology needs and its perceived usability. Experiments were conducted in the USA, Korea and China, including 24 American, 23 Korean and 21 Chinese older adults. Main findings include: Chinese and Korean participants exhibited significantly higher degrees of interest, intention and self-estimated frequency of using information technology to connect with others than the US participants; the US participants showed more interest in and intent to use information technology to access information than to connect with others. The results suggest that older adults' cultural backgrounds are important in the design of IT products.